FREQUENCY OF DEPRESSION IN EPILEPSY: A HOSPITAL BASED STUDY - Yousafzai, Aziz -ur-Rehman; Yousafzai, Abdul Wahab; Taj, Rizwan (Journal of Ayub Medical College Abbottabad, 2009)
Background: Depression is the most frequent psychiatric morbidity among epileptic patients adversely affecting their quality of life. It has also been associated with deliberate self harm and suicide. The objectives of this study were to know the frequency of depression in epileptic patients coming to neurology clinic of tertiary care hospital and also to find an association of clinical and demographic variables of epileptic patients with depression. Methods: Convenient sampling method was used to select patients after informed consent. Depression was diagnosed using semi structured interview based on ICD-10. Data was analyses using SPSS version 10.0, and analysis carried out using descriptive and inferential statistics. Chi-square test of association was applied to see the significance. Result: Out of total 100 patients 55% were males, 47% were married and mean age of the patients was 25.5±4.34 years. About 60% patients were found depressed at the time of interview. Male patients, being married and coming from low socioeconomic stratum were significantly associated with depression. None of the patient was on anti-depressant medication. Conclusion: Depression was found to be highly prevalent psychiatric morbidity in epileptic patients. Men, married status, uncontrolled epilepsy and low socioeconomic group more prone to have depression. Keywords: Depression, Epilepsy, Suicide